Selective Oxidation of 1-Tetralones to 1,2-Naphthoquinones with IBX and to 1,4-Naphthoquinones with Oxone® and 2-Iodobenzoic Acid - Ren, Jiangmeng; Lu, Lei; Xu, Junchao; Yu, Tianyin; Zeng, Bu-Bing (Synthesis, 2015)
The preparation of naphthoquinones by oxidation of 1-tetralone derivatives is reported. 1,2-Naphthoquinones were prepared by oxidation with IBX and 1,4-naphthoquinones were prepared by oxidation using Oxone® and 2-iodobenzoic acid. The mechanistic pathways are also discussed.
Keywords: selective oxidation; IBX; 1,2-naphthoquinones; 1,4-naphthoquinones; hypervalent iodine reagents